PARTISIPASI POLITIK MASYARAKAT PERBATASAN NEGARA DALAM PILKADA SERENTAK DI KABUPATEN MALINAU - Semuel Risal; Eka Pratiwi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
The purpose of this study is to describe and analyze the low level of political participation of state border communities as an evaluation of the implementation of the elections held by the Malinau Regional Election Commission in 2015. There is a tendency that border communities do not care about democratic parties (elections) being held, because they feel ostracized by the government, even most of their basic needs depend on neighboring countries, namely Malaysia. While the Indonesian government seems to be ignoring border communities with high living costs and low welfare levels. Giving the impression that the election results also did not have an impact on the lives of the people of the country's borders. Whereas one of the objectives of the implementation of the elections is to produce elections that have clean, honest and fair integrity in order to be able to produce qualified leaders to develop community welfare. The results showed that social, economic, geographical, administrative and community apathy conditions affected the level of political participation of people at the border. Community apathy and geographical conditions have a considerable impact, so the development of border communities needs to be an important concern of the government so that the people trust the government. Thus, the awareness of the people of the national borders to build their participation in determining their leaders in the future elections.